(untitled) (DAPesquisa, 2021)
Currently in the market culture, it is possible to see graphic brands of fashion brands stamping products, being also publicly exposed as symbols that identify, differentiate and represent their users. This movement, demonstrating an identification and a tacit agreement of correlation between the public exposure of the individual with a brand, due to this form of identity expression that, at the same time, differs and represents the product and the user. This article, an exploratory descriptive-qualitative study of the phenomenon called "Logomania", thus, as a special reference for fashionists, the graphic brands of brands are publicly exposed as entities of worship and devotion, which notes this "logomaniac" movement as a means of identifying users, commonly observed in the fashion media and consequently in the urban scene. From the argument through the theoretical-marketing foundation to the concept of research methods to the study, it is proposed to present the indicated phenomenon, with a review and the application of the system of concepts and theoretical social contributions linked to it to considerations involving Media , Fashion, Brand and Market Culture.